Comparative In Vitro Activities of New Antibiotics for the Treatment of Skin Infections. (8th April 2019) - Shortridge, Dee; Flamm, Robert K
Abstract: Bacterial skin infections result in significant morbidity and have contributed to enhanced health-care resource utilization. The problem is heightened by emerging antimicrobial resistance. Multiple novel agents active against resistant pathogens that cause skin infections—including dalbavancin, tedizolid phosphate, oritavancin, and delafloxacin—have been approved over the past 5 years. Common features of these agents include gram-positive activity and favorable safety. Of these agents, delafloxacin is unique in being active against both gram-positive and gram-negative pathogens that cause skin infections, including those resistant to other antimicrobial agents. It is, therefore, an effective option for the treatment of skin infections.